PERAN ANTIBODI KUNING TELUR (IgY) SEBAGAI OPSONIN UNTUK PENCEGAHAN SERANGAN MUTAN STREPTOCOCCUS SEROTIPE D (STREPTOCOCCUS SOBRINUS) - Okti Nadia Poetri; Retno D. Soejoedono; Agustin Indrawati; I Wayan T. Wibawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The aim of this study was to explore the role of serotype d Mutan Streptococcus (Streptococcus sobrinus) spesific immunoglobulin Y (IgY-Ss) as opsonin against the same strain. The eggs were collected from Single Comb Brown Leghorn which has been immunized with Streptococcus sobrinus. Agar gel precipitation test was applied to detect IgY-Ss in serum and egg. Egg containing IgY-Ss was collected and extracted by PEG-Amonium sulphate and purified using fast protein liquid chromatography. The purity of IgY-Ss was determined by UV spectrophotometer. Molecular weight was established by SDS-PAGE (sodium dedocyl sulphate-poly acrilamide gel electrophoresis). Biological activities of IgY-Ss as opsonin was determined by phagocytosis assay. Phagositic activity of macrophages was not increased by preincubation of both S. sobrinus (107 CFU/ml) and 100 μg of IgY-S, however the phagositic capacity was increased from 1.6 bacterial cell/ macrophag to 5.17 bacterial cell/ macrophag. These finding suggest that IgY-Ss obtained from hens immunized with S. sobrinus provide an alternative to prevent S. sobrinus infection.